Dynamic outgassing of deuterium, helium and nitrogen from plasma-facing materials under DEMO relevant conditions. (1st November 2016) - Möller, S.; Matveev, D.; Martynova, Y.; Unterberg, B.; Rasinski, M.; Wegener, T.; Kreter, A.; Linsmeier, Ch.
Abstract: In confined plasma magnetic fusion devices significant amounts of the hydrogen isotopes used for the fusion reaction can be stored in the plasma-facing materials by implantation. The desorption of this retained hydrogen was seen to follow a t α law with α   ≈  −0.7 in tokamaks. For a pulsed fusion reactor this outgassing can define the inter-pulse waiting time. This work presents new experimental data on the dynamic outgassing in ITER grade tungsten exposed under the well-defined conditions of PSI-2 to pure and mixed D2 plasmas. A peak ion flux of 10 22 D + m −2 s is applied for up to 6 h at sample temperatures of up to 900 K. Pure D2 and mixed D2   +  He, D2   +  N2 and D2   +  He  +  N2 plasmas are applied to the sample at 68 V bias. The D2, He, N outgassing at 293 K and 580 k are observed via in-vacuo quadrupole mass spectrometry covering the range of 40 s–200 000 s after exposure. The outgassing decay follows a single power law with exponents α   =  −0.7  to  −1.1 at 293 K, but at 580 K a drop from α   =  −0.25 to  −2.35 is found. For DEMO a pump-down time to 0.5 mPa in the order of 1–5 h can be expected. The outgassing is in all cases dominated by D2 .